The formation of aromatic hydrocarbons during the pyrolysis of polyethylene - Choo, W.; Tang, L.; Rownaghi, A.; Yong, H.; Li, Chun-Zhu; Bhattacharya, S. (ICMS Pty Ltd, 2010)
Plastics see very widespread use in modern society. The properties of many plastics can be modified relatively easily to fit a wide variety of applications. However, the disposal of waste plastics presents a significant environmental challenge. Recently, there has been considerable interest into tertiary recycling of waste plastics to produce liquid fuel. This project focuses on the formation of aromatic hydrocarbons during thermal pyrolysis of plastics. Several reactor configurations have been suggested for the pyrolysis of plastics. The reactor configuration used in this study consists of a stirrer tank reactor coupled with a reflux column and a condenser.